A Comparative Study of the Simple Clause in Akan, Dagaare and English - Abunya, Levina Nyameye; Owusu, Edward; Naapane, Faustina Marius (Education and Linguistics Research, 2024)
The paper compares how the simple clause is expressed in Akan (Kwa, Niger-Congo), Dagaare (Gur, Niger-Congo) and English. It examines the simple clause in relation to noun phrase, verbal phrases, adpositional phrases, basic word order in declarative and focus constructions, and the basic locative construction. Basically, the study reveals that despite the differences, Akan and Dagaare have a lot in common as compared to English. This of course shows how distant English is from the two African languages. Certain linguistic features such as serial verb construction and focus constructions were unique to Akan and Dagaare and this, is not surprising since languages within the same language family (Niger Congo) tend to share certain lexical, phonological, morphological and syntactic features. The significant variation between these languages shows where Akan and Dagaare languages diverge into other sub-family groups: Kwa and Gur, respectively.